The Effects of Nudges: One-Shot Only? Exploring the Temporal Spillover Effects of a Default Nudge - Van Rookhuijzen, Merije; De Vet, Emely; Adriaanse, Marieke A. (Frontiers in Psychology, 2021)
Nudges, such as defaults, are generally found to be effective in guiding immediate behavioural decisions. However, little is known about whether the effect of a nudge can be lasting, meaning that it spills over to subsequent similar choices without the nudge present. In three experiments, we explored the temporal spillover effect of a default nudge. Results of Experiments 1 (N = 1077) and 2 (N = 1036) suggest that nudging participants into completing a longer questionnaire affected their decision for the same behaviour a day later without a nudge present. However, nudging participants into a healthier food choice in Experiment 3 (N = 969) did not result in such a temporal spillover effect. Results indicated that participants’ changed attitude towards the nudged behaviour may partly explain the temporal spillover effects. These findings suggest that for some, but not all behaviours, default nudges may have the potential to yield temporal spillover effects and warrant a further investigation of boundary conditions and facilitators of spillover effects of nudges.